Self-transcendence values, initial perceptions of relationship quality, and reference points in a distributive negotiation - Cardador, Joe M., author; Thornton, George, III, advisor; Bell, P. A., committee member; Chen, Peter, committee member (Colorado State University. Libraries, 2003)
The present study used structural equation modeling (SEM) to examine a model of antecedents and consequences of perceptions of relationship quality with a negotiation partner. Partner values were manipulated to be either low or high in Self-transcendence under two negotiation contexts: cooperative and competitive. Desirability of Self-transcendence (ST) values and perceptions that a negotiation partner held these values interacted to influence perceptions of Relationship Quality, although the main effect for perceptions of a partner's ST accounted for most of the variance in Relationship Quality. An analysis of the interaction suggested that probability that a partner held ST values was more positively related to Relationship Quality when ST values were more desirable. Perceptions of Relationship Quality were hypothesized to influence a negotiator's reference points and intention to exchange information with a partner, and the negotiation context (cooperative or competitive) was expected to moderate these relationships. Relationship Quality was significantly related to initial offers made to a partner, intention to ask about a partner's break-even point, and intentions to reveal one's own break-even point; however, the negotiation context did not moderate these relationships. Post-hoc analyses suggested that relationship quality mediated the influence of the probability that a partner endorsed ST values and intention to reveal one's break-even point. Further, when desirability of ST values, probability that a partner was high in ST values, and an interaction term for these latent variables was used to predict Aspirations, the path between the interaction latent variable and Aspirations was significant. An analysis of the interaction suggested that negotiators desiring a partner high in ST values that were in fact partnered with such an individual were more likely to have lower aspirations for the negotiation. Overall, results suggest that information on a partner's values in a negotiation context influences perceptions of Relationship Quality for unacquainted negotiators and that Relationship Quality perceptions influence negotiation intentions. Areas for further research based on these findings are suggested.
Keywords: social psychology; statistics